2006
DOI: 10.1109/dac.2006.229426
|View full text |Cite
|
Sign up to set email alerts
|

A thermally-aware performance analysis of vertically integrated (3-D) processor-memory hierarchy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…We will show that by considering more memory controllers as well as aggressive operating frequencies, the speedup offered by 3D integration becomes much greater as long as the associated heat dissipation can be managed via micro-fluidic cooling. The work by Loi et al has demonstrated that memory bound programs can get performance improvements of 3x or more by stacking DRAM on logic, but that for CPU bound programs, degradation actually occurs by going to a 3D implementation due to temperature increases [11]. These results are consistent with our finding, which is that 3D integration can only offer performance increases when sufficient cooling is applied to the chip.…”
Section: Previous Worksupporting
confidence: 94%
“…We will show that by considering more memory controllers as well as aggressive operating frequencies, the speedup offered by 3D integration becomes much greater as long as the associated heat dissipation can be managed via micro-fluidic cooling. The work by Loi et al has demonstrated that memory bound programs can get performance improvements of 3x or more by stacking DRAM on logic, but that for CPU bound programs, degradation actually occurs by going to a 3D implementation due to temperature increases [11]. These results are consistent with our finding, which is that 3D integration can only offer performance increases when sufficient cooling is applied to the chip.…”
Section: Previous Worksupporting
confidence: 94%
“…Performance analysis for 3D systems with on-chip DRAM typically focuses on comparing the system performance between 2D and 3D systems. Loi et al show that on-chip memory delivers significant amount of speedup for three SPEC benchmarks [3]. Liu et al report up to 126% speedup for single-core processors with 3D memory stacking [2].…”
Section: Related Workmentioning
confidence: 98%
“…Recently, several research groups have introduced approaches for modeling performance in 3D systems, focusing on a small number of cores (single-core, quad-core) and single-threaded workloads [2], [3], [4]. Thermal hotspots have been a pressing issue due to the cooling costs and reliability challenges in conventional 2D design as well as 3D systems.…”
Section: Introductionmentioning
confidence: 99%
“…For its numerous opportunities, it attracts substantial number of researches from industry and academia of 3D stacking. Bryan et al have evaluated the 3D stacking in terms of power and performance [1], and Loi et al have analyzed the processor-memory hierarchy using 3D technologies for performance and thermal perspectives [2]. Also, Black et al have researched on die stacking 3D microarchitecture made up only SRAM or DRAM [9].…”
Section: Related Workmentioning
confidence: 99%
“…Remarkable strength of 3D integration is additional reduction of area size, wire length, and performance progress. Heterogeneous memory dies in different memory types, such as dynamic random access memory (DRAM), magnetic random access memory (MRAM) and phase change random access memory (PRAM), can be stacked on a microprocessor [1,2].…”
Section: Introductionmentioning
confidence: 99%